2018
DOI: 10.1097/j.pain.0000000000001340
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain clinical trials: factors associated with decreases in estimated drug efficacy

Abstract: Multiple recent pharmacological clinical trials in neuropathic pain have failed to show beneficial effect of drugs with previously demonstrated efficacy, and estimates of drug efficacy seems to have decreased with accumulation of newer trials. However, this has not been systematically assessed. Here, we analyze time-dependent changes in estimated treatment effect size in pharmacological trials together with factors that may contribute to decreases in estimated effect size. This study is a secondary analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 33 publications
(39 reference statements)
6
101
0
15
Order By: Relevance
“…Identification of mechanisms that underlie the development and persistence of back pain presentations, and the development of and testing of ways to better match treatment to patients, are both internationally agreed research priorities 14 . There are specific medication options for patients with neuropathic pain, based on underlying mechanisms that may M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 7 accompany nerve damage 20 and these are advocated for patients (including those with sciatica) consulting in primary care 43,44 . Recognising neuropathic pain in LBLP patients in primary care is important as this may facilitate timely access to recommended medications, if deemed appropriate, which in turn may contribute to better outcomes for these patient.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of mechanisms that underlie the development and persistence of back pain presentations, and the development of and testing of ways to better match treatment to patients, are both internationally agreed research priorities 14 . There are specific medication options for patients with neuropathic pain, based on underlying mechanisms that may M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 7 accompany nerve damage 20 and these are advocated for patients (including those with sciatica) consulting in primary care 43,44 . Recognising neuropathic pain in LBLP patients in primary care is important as this may facilitate timely access to recommended medications, if deemed appropriate, which in turn may contribute to better outcomes for these patient.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…With the addition of appropriate findings from diagnostic tests, a patient can meet the criteria for probable neuropathic pain. When clinical examination is not possible in epidemiological research, (for example, Torrance et al 54 and VanDenKerfhof et al 60 ) neuropathic case ascertainment tools use self-reported neuropathic characteristics (for example, Self-report version of Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS) 8 to identify, at best, possible cases of neuropathic pain 20,52 .…”
Section: Introductionmentioning
confidence: 99%
“…Como sabemos, el dolor neuropático es un trastorno de dolor crónico debilitante y presenta unas necesidades médicas insatisfechas (7). La mayoría de los medicamentos utilizados para el tratamiento del dolor neuropático tienen limitados la dosis efectiva por efectos secundarios, por lo que se necesitan fármacos efectivos sin los efectos secundarios sistémicos (8). Los datos publicados sugieren que la toxina botulínica tipo A tiene efectos analgésicos contra el dolor neuropático periférico (3,8).…”
Section: Sr Directorunclassified
“…Se identificaron dos ensayos controlados aleatorios adicionales que cumplieron con los criterios de calidad, pero estos estudios se centraron específicamente en la neuralgia del trigémino, que está fuera de los criterios de inclusión de este estudio que acabamos de comentar. La evidencia existente es compatible con el uso de antidepresivos tricíclicos, antidepresivos inhibidores de la recaptación de serotoninanoradrenalina, pregabalina, gabapentina (incluyendo la formulación de liberación prolongada) y enacarbil gabapentina, tramadol, opioides fuertes y los tratamientos tópicos, apósitos de lidocaína 5 % y parches de capsaicina 8 % para el tratamiento de dolor neuropático periférico (8).…”
Section: Evidencia Científica Disponible De La Toxina Botulínica En Dunclassified
See 1 more Smart Citation